2007
DOI: 10.1097/hjr.0b013e32828622e8
|View full text |Cite
|
Sign up to set email alerts
|

Relation of depression to various markers of coagulation and fibrinolysis in patients with and without coronary artery disease

Abstract: Our study gives no evidence that there is a significant relation among depression, CAD, and blood coagulation and fibrinolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
2
26
3
Order By: Relevance
“…Using mediation analysis, these studies showed that factors of an unhealthy lifestyle; increased BMI or weight gain, smoking and being inactive, explained the association between CRP levels and depressive symptoms. The finding that both depression and anxiety were not related to fibrinogen levels are not consistent with some previous reports [20], but is in line with others [12,14]. Relatively small effect sizes have been observed in a cohort with people with clinical depression; with adjusted models showing that current depression in men, but not women, was associated with CRP [21].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Using mediation analysis, these studies showed that factors of an unhealthy lifestyle; increased BMI or weight gain, smoking and being inactive, explained the association between CRP levels and depressive symptoms. The finding that both depression and anxiety were not related to fibrinogen levels are not consistent with some previous reports [20], but is in line with others [12,14]. Relatively small effect sizes have been observed in a cohort with people with clinical depression; with adjusted models showing that current depression in men, but not women, was associated with CRP [21].…”
Section: Discussionsupporting
confidence: 56%
“…Patients were contacted via mail or telephone within three months after CAG or CT. Questionnaires were sent and returned by postal mail. Hospital records were screened for clinical information and blood was collected at the hospital during morning office hours (8)(9)(10)(11)(12). The study was performed in accordance with the declaration of Helsinki and approved by the local Institutional Review Board (Protocol number: NL22258.008.08).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in several other studies of ACS populations, D-dimer levels did not yield prognostic information. [37][38][39][40] In the present population, D-dimer showed no independent prognostic utility at 2 years of follow-up, 28 but gained prognostic importance during the extended follow-up period, reflecting a gradual progression of disease from silent to clinically evident thrombotic manifestations. In contrast to PTX3, hsCRP did not appear to be an independent predictor of total mortality in our multivariate analysis, but its level was associated with recurrent MI during the follow-up period.…”
Section: Discussioncontrasting
confidence: 53%
“…via increased platelet activity, inflammation, alterations in the hypothalamic–pituitary–adrenal axis or increased activity of the sympathetic nervous system). 48 However, the causal role of depression remains debated because the observational evidence is not entirely consistent 9 and because experimental studies of the effects of depression treatment on cardiovascular outcomes produced ambiguous results. 1013 Another question relates to whether mortality is associated only with severe depression or whether it is also predicted by milder symptoms of psychological distress.…”
Section: Introductionmentioning
confidence: 99%